2019
DOI: 10.2147/idr.s190245
|View full text |Cite
|
Sign up to set email alerts
|

<p>Molecular epidemiology and resistance profiles among healthcare- and community-associated <em>Staphylococcus aureus</em> keratitis isolates</p>

Abstract: Purpose To characterize the molecular, epidemiological, and resistance profiles of methicillin-resistant (MRSA) and methicillin-susceptible (MSSA) keratitis isolates. Patients and methods We used a combination of standard microbiological techniques and DNA microarray analysis to characterize the molecular and antibiotic resistance profiles of 75 Staphylococcus aureus keratitis isolates collected over an 11-year period (2006–2016). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
3
19
1
2
Order By: Relevance
“…This aligns nearly identically with the recent report of 56 ocular isolates collected from Massachusetts Eye and Ear Infirmary that demonstrated 23.2% ST5, 16% ST8 and 11% ST30 [13]. Similarly, a set of 75 S. aureus keratitis isolates collected from the University of Miami, Bascom Palmer Eye Institute, included 40% isolates of clonal complex (CC) 5 (ST5 is classified within CC5), and 37.3% of CC8 (ST8 is classified within CC8) [16]. Interestingly, only one isolate from this study set was identified in clonal complex 30.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This aligns nearly identically with the recent report of 56 ocular isolates collected from Massachusetts Eye and Ear Infirmary that demonstrated 23.2% ST5, 16% ST8 and 11% ST30 [13]. Similarly, a set of 75 S. aureus keratitis isolates collected from the University of Miami, Bascom Palmer Eye Institute, included 40% isolates of clonal complex (CC) 5 (ST5 is classified within CC5), and 37.3% of CC8 (ST8 is classified within CC8) [16]. Interestingly, only one isolate from this study set was identified in clonal complex 30.…”
Section: Discussionsupporting
confidence: 83%
“…Much is still unknown regarding the mechanisms by which S. aureus can establish and maintain infections in the eye, however, initial studies have begun to identify specific strain types as well as virulence factors that may be particularly important in ocular disease. For example, multilocus sequence typing (MLST), which compares the genetic sequences of seven housekeeping genes (arcC, aroE, glpF, gmk, pta, tpi, and yqiL) to identify sequence types (STs), has revealed ST5, ST8, ST15, ST30, ST59, and ST772 as common among specific S. aureus ocular strain sets [13][14][15][16]. Additionally, studies to assess the prevalence of S. aureus virulence factors among ocular isolates such as Panton-Valentine Leukocidin (pvl), Enterotoxin E (sea) or Leukocidin E (lukE) have demonstrated that while pvl and lukE are found in the majority of sampled ocular strains, sea may be less common [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in addition to PVL binding to retinal ganglion cells, the toxin also co-localized to horizontal cells which did not express C5a receptor, and there was no significant increase in IL-6 as compared to the control explants. Peterson et al [101] recently reported that the PVL gene was detected in only 14.7% of S. aureus keratitis isolates in their study, so it is unclear how clinically relevant this toxin is to ocular disease.…”
Section: Bi-component Toxinsmentioning
confidence: 99%
“…The acquisition of the mecA or mecC genes, which lead to alternative penicillin-binding proteins, account for the most common mechanism of resistance that results in the methicillin-resistant phenotype [ 6 , 7 , 8 , 9 ]. Although historically considered a hospital-acquired infection, MRSA clones are increasingly being encountered among community infections [ 10 , 11 , 12 ]. MRSA is known to cause a variety of ocular infections, including keratitis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%